Daily-Life Social Experiences as a Potential Mediator of the Relationship Between Parenting and Psychopathology in Adolescence - Achterhof, Robin; Kirtley, Olivia J.; Schneider, Maude; Lafit, Ginette; Hagemann, Noëmi; Hermans, Karlijn S. F. M.; Hiekkaranta, Anu P.; Lecei, Aleksandra; Myin-Germeys, Inez (Frontiers in Psychiatry, 2021)
Adolescence is a vulnerable period for psychopathology development, and certain parenting styles are consistent and robust predictors of a broad range of mental health outcomes. The mechanisms through which maladaptive parenting styles affect the development of psychopathology are assumed to be largely social in nature. Yet, the social mechanisms linking parenting to psychopathology are unexplored at arguably the most important level of functioning: daily life. This study aims to identify the associations between three parenting styles, and the experience of daily-life social interactions. Furthermore, we aim to explore the extent to which these parenting styles and altered daily-life social experiences are associated with psychopathology. In this study, we recruited a sample of N = 1,913 adolescents (63.3% girls; mean age = 13.7, age range = 11 to 20) as part of the first wave of the longitudinal cohort study “SIGMA”. Parenting styles (psychological control, responsiveness, and autonomy support) and psychopathology symptoms were assessed using a retrospective questionnaire battery. The experienced quality of social interactions in different types of company was assessed using the experience sampling method, ten times per day for 6 days. Direct associations between parenting styles and general quality of daily-life social experiences were tested using a three-level linear model, revealing significant associations between social experiences and different parenting styles. When interaction effects were added to this model, we found that maternal responsiveness and paternal psychological control mainly related to altered qualities of social interactions with parents, while paternal autonomy support was associated with better experiences of non-family social interactions. Finally, an exploratory path analysis highlighted how both paternal autonomy support and altered quality of non-family interactions are uniquely associated with psychopathology levels. These findings demonstrate the general and pervasive effects of maladaptive parenting styles, as parenting seems to broadly affect adolescents' interactions with different types of social partners in everyday life. Moreover, they illustrate a potential mediated relationship in which altered daily-life social interactions could drive the development of psychopathology. A stronger focus may be required on the role of altered day-to-day social experiences in the prevention and potentially, the treatment, of adolescent psychopathology.